Development of a Checklist of Potentially Traumatic Events in Children and Adolescents (CEPT-CA) - Inês Barroca; Catarina Melo Santos; Ana Velosa; Gonçalo Cotovio; Kasia Kozlowska; Inês Pinto; Paula Saraiva Carvalho (Karger Publishers, 2022)
Introduction: Since exposure to potentially traumatic events during childhood and adolescence has been shown to be very common, its screening is very important. Our aim was to develop a self-assessment checklist to perform screening of potentially traumatic events in childhood and adolescence. Methods: The development of the Checklist of Potentially Traumatic Events in Children and Adolescents (CEPT-CA) was based on: (a) the structure of Life Events Checklist that has been translated, back-translated, and adapted; (b) recommendations of renowned entities about trauma in childhood; (c) particularities of potentially traumatic events in childhood; (d) adapting the language to the target population's age group; (e) Portugal's sociocultural context. The preliminary version of the CEPT-CA was again discussed with the Review Committee. Subsequently, a pre-test was carried out with 30 children/adolescents between the ages of 7 and 18 years. Results: The CEPT-CA includes the assessment of 16 potentially traumatic events. It also includes a 17th item, in which "any other very difficult/stressful event" may be added. Each event can be selected according to "It happened to me," "I saw it happen to someone else," "They told me," "I'm not sure," and "Not applicable." The mean time to complete the questionnaire was 9 min. Conclusion: This pioneering study presents a checklist of potentially traumatic events in childhood/adolescence. This tool is useful for tracking these traumatic events, thereby allowing an early and specific assessment and intervention.